A Review about Mixed Convection Resulted From Buoyancy Forces and Moving Wall in Cavities (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Over the past few years, a considerable number of scholars have been diligently investigating forced and mixed convection in containers, irrespective of whether the walls were stationary or mobile. Therefore, they have experimented with several thermal boundary conditions and geometries in order to achieve the best possible outcomes utilizing sophisticated analytical techniques. Many researchers have employed various methods to promote the transfer of heat via mixed convection in lid-driven cavities.